Evolution of payment for ecosystem services in the Pixquiac sub-basin, Veracruz, Mexico - Chablé-Rodríguez, Gabriel; González-Guillén, Manuel de J; González-Martínez, Teresa M; Gómez-Guerrero, Armando; Fernández-Reynoso, Demetrio S (BOSQUE, 2023)
Payment for ecosystem services (PES) is an economic tool that seeks to compensate landowners for the conservation of their forested lands and reduce the negative impacts of land use change in forest areas that are important for the provision of ecosystem services (ES). However, it is essential to verify that the implementation of this mechanism is focused on where it is most needed. In this study, an analysis of the evolution of PES in the Pixquiac sub-basin in Veracruz was carried out, and the degree of coincidence between the supported areas and hydrological priority areas was evaluated. Information regarding the fiscal years of PES in the region from 2003 - 2016 was statistically analyzed, and the priority areas and areas of PES were determined using geographic information systems. Results showed that payments amounted to USD 1,076,782 in an area of 5,450 ha during the period analyzed. However, only 881.58 ha (24.5 % of the total hydrological priority areas) were considered in this payment scheme. Decision-makers must have up-to-date information that allows them to focus available resources at a more precise spatial scale. In addition, efforts must be made by the actors involved to ensure greater participation by forest owners and ecosystem service users.